Retrospective Observational Study of Ultrasonography for Molar Pregnancy in Nangarhar, Afghanistan - Teaching Assistant Drs. Wahida Ahmady; Teaching Assistant Dr. Shah Agha Salehi; Teaching Assistant Dr. Sayed Azizullah Hashimi (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2021)
Introduction: The primary aims of this study were to establish what proportion of ultra-sonographic suspected molar pregnancies and to review the features of these scans to help identify criteria that may improve ultra-sonographic diagnosis. This was a retrospective observational study conducted in the Early Pregnancy in Nangarhar University Teaching Hospital over in 2-year period. Cases of ultrasonographically suspected to molar pregnancy or other gestational trophoblastic disease were identified. In addition, cases which were diagnosed on histopathology that were not suspected on ultrasound were also examined. In discrepant cases, the images were reviewed unblended by two senior sonographers. Statistical analysis for likelihood ratio and post-test probabilities was performed. There was a total of 18864 pregnancies during the study period seventy-two women had gestational trophoblastic disease suspected on ultrasound examination (1:262, 0.38%) 53/72 (73.6%) had histologically confirmed gestational trophoblastic disease, Sensitivity was 73.6% with an estimated specificity of 99.7%. 72 molar pregnancies were suspected on pre-op ultrasound; 43/72 of complete moles were suspected on pre-op ultrasound, compared with 16/72 of partial moles. On retrospective review of the pre-op ultrasound images, there were cases that could have been suspected prior to surgery. Detecting molar pregnancy by ultrasound remains a diagnostic challenge, particularly for partial moles. These data suggest that there has been an increase in both the predictive value and the sensitivity of ultrasound over time, with a high LR and post-test probability; however, the diagnostic criteria remain ill-defined and could be improved.